Dissociation of Antithrombotic Effect and Bleeding Time Prolongation in Rabbits by Inhibiting Tissue Factor Function - Himber, Jacques; Kirchhofer, Daniel; Riederer, Markus; Tschopp, Thomas B; Steiner, Beat; Roux, Sébastien P (Thrombosis and Haemostasis, 1997)
Inhibition of the tissue factor/factor Vila (TF/F. Vila) complex attenuates thrombosis in different animal models of arterial thrombosis. However, it remains unclear to what extent the antithrombotic effects are associated with changes in hemostatic functions and how this compares with inhibition of thrombin, an enzyme acting at a later stage in the coagulation cascade. The antithrombotic and the antihemostatic effects of a monoclonal anti-TF antibody (AP-1) were compared in a model of arterial thrombosis to those of a direct thrombin inhibitor (napsagatran) and heparin. In anesthetized rabbits transient arterial thrombi were induced by mechanical damage to the subendothelium of a moderately stenosed carotid artery. Recurrent formation and dis lodgement of thrombi resulted in cyclic flow variations (CFVs) which were monitored over 2 hours. Rabbits received intravenously either a placebo (control), a monoclonal anti-rabbit TF antibody (AP-1, 05 mg/kg as an i.v. bolus repeated every 15 min, a specific low molecular weight thrombin inhibitor (napsagatran, 3 fxg/kg/min) or heparin (3 and 13 fig/kg/min). The effect of the inhibitors on the hemostatic system was studied in a separate set of rabbits by measuring template bleeding times (BT) in the ear arterioles, marginal ear vein and the nail cuticle of the foreleg. AP-1 and napsagatran showed a similar antithrombotic activity (78% and 80% abolition of the CFVs, respectively), whereas either low or high dose heparin was poorly effective (43 % and 40% inhibition of CFVs, respectively). At these antithrombotic doses and even at 4-fold higher dosage, AP-1 did not significantly alter the BT, whereas napsagatran and heparin prolonged the ear vessels and cuticle BT in a dose-dependent manner. These results suggest that in contrast to direct thrombin inhibition, the blockade of the TF/F. Vila function did not result in a concomitant prolongation of the bleeding time. Thus, dissociation of antithrombotic and antihemostatic effects indicates that inhibition of the coagulation system at its initial stage represents a promising approach for the development of new anticoagulants.